Strategy For Development Of Micro/Small/Medium Enterprises (MSMEs) Based On A Circular Economy: Case Study MSMEs In Mataram - Pratiwi, Intan Kusuma; Iva Istirawati (IQTISHADUNA, 2024)
This research examines 2 main issues, 1) strategies for developing Micro, Small and Medium Enterprises (MSMEs) in the City of Mataram, 2) supporting and inhibiting factors for the development of Micro, Small and Medium Enterprises (MSMEs) in the City of Mataram. This research uses a qualitative type using three types of data collection models, namely observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Meanwhile, checking the validity of the data uses extended observations, increasing persistence and triangulation. From the results of the research that has been carried out, it was found that the development strategies for Micro, Small and Medium Enterprises (MSMEs) in the City of Mataram are different for each MSME. There are those who adopt all circular economy principles or several principles of the circular economy. The 5 principles are: Reduce, Reuse, Recycle, Recover, Redesign. Meanwhile, the supporting and inhibiting factors for the development of Micro, Small and Medium Enterprises (MSMEs) inMataram City vary in the process of running the business. From the supporting factors for the development of MSMEs, it can be concluded that the important points are production materials, human resources and information technology. Meanwhile, the factors inhibiting the development of MSMEs are business capital, regulations, resistance and new competitors